Mapped Municipal Debt Records (U.S. Local Governments, 2000–2023) - Duane Ebesu (21583046) (2025)
This database consists of structured records of U.S. municipal debt offerings during 2000 through 2023. Each row corresponds to a unique municipal bond offering and covers variables of measurement of issuance date, jurisdiction identifiers (e.g., county, city, state), bond characteristics (e.g., maturity, par value, coupon rate, proceeds use), and geospatial mapping fields of references of their municipal project locations. This data was cleaned, standardized, and geocoded for assembly with resilience investment records and U.S. federal grant awards. Its primary purpose is to enable empirical work on climate-related fiscal vulnerability and economic impacts of adaptation measures like nature-based solutions (NbS). This corresponds to broader work on tracking interactions of local debt trends with the federal climate resilience awards and local credit performance.